Molecular and biological characterization of a putative new sobemovirus infecting Physalis peruviana - Farina A.E. (2019)
© 2019, Springer-Verlag GmbH Austria, part of Springer Nature.Physalis peruviana is a perennial solanaceous plant that has recently been established as a commercial crop in Brazil. This work reports the near-complete genome sequence, particle morphology, and plant host responses to a putative new sobemovirus, named “physalis rugose mosaic virus”. The virus, characterized by isometric particles of ca. 30 nm in diameter, causes foliar symptoms of mosaic, malformation and blistering, accompanied by stunting. The near-complete genome sequence comprises 4175 nucleotides and contains five open reading frames that are similar to those of other sobemoviruses. In addition to P. peruviana, the new virus systemically infected Capsicum annuum, Nicotiana tabacum and Solanum lycopersicum by mechanical inoculation. Thus, this virus may cause disease in these crops in the field.